2017
DOI: 10.1371/journal.pone.0174619
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality and suicide attempt among adults with internet addiction: A nationwide community sample of Korea

Abstract: PurposeInternet addiction (IA) is defined as a psychological dependence on the internet, regardless of the type of activities once logged on, and previous studies have focused on adolescents and young adults. The aim of this study was to investigate the association between suicide attempts and sleep among community-dwelling adults with IA.MethodsThe Young’s Internet Addiction Test (IAT), the Korean version of the Composite International Diagnostic Interview (K-CIDI) and a suicide questionnaire were used in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 53 publications
4
42
0
5
Order By: Relevance
“…The negative impact of internet abuse on both sleep duration and sleep quality has been previously described in the literature. 38 For example, Kim et al 39 found that Korean subjects with internet addiction were 1.7 times more likely to experience poor sleep quality in comparison to those with normal internet use. Also, subjects who spent more time in the web have more (2.5 times higher) risk of developing depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of internet abuse on both sleep duration and sleep quality has been previously described in the literature. 38 For example, Kim et al 39 found that Korean subjects with internet addiction were 1.7 times more likely to experience poor sleep quality in comparison to those with normal internet use. Also, subjects who spent more time in the web have more (2.5 times higher) risk of developing depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This association is in line with the findings reported in previous studies. 7,[12][13][14][15][16][17][18][19] One of the possible reasons for the associated psychological co-morbidities is the disrupted sleep-wake cycle and a higher rate of insomnia among heavy internet users. 19 In this study, the participants reported night time as the preferred time of internet use and some of them even used to spend the whole night online which substantiates the plausible association above.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of IA was estimated to be 9.8%–15.2% in the United States among people in their teens and 20s . IA not only encompasses psychological reliance, but also causes physiological disorders, such as musculoskeletal symptoms and sleep disturbance . Changes in autonomic nervous system functions were also reported in school‐aged children with IA …”
Section: Introductionmentioning
confidence: 97%